FORMATION OF TROPICAL CYCLONES IN THE BAY OF BENGAL (MAUSAM, 1994)
of Rengal. For th is purpose, the Ilay of Bengel is divided into number of one degree lat itud eIOlljlilUJcsqua re- crib and the Ic rmetion prob abilities WMe found in each of these cells in different months of bestmonsoon an ti pre-monsoon 30 th et il will help in formul ation of long term plan for the natura l d isa ster redu crion.Ino rde r 10 lind OUI the la titud inal variation offhe formation o rcyclonic stonns. the Bay o( Btnaal is aaain d ivided into(our sectors with a wi dth o f S-d ("~rte lo ngitude sectors. namely. 80-85. 85-90, 90-9S and 9SoI00. In (hue sectors themeanloca tion s of'fonnation in terms of'Iatitude was ca lcula ted and discussed . Furt her, the Bay is sub-divided into 14division s 10 lin.t out the possible spa tial va ria lions using sta tisl ical lech niques.Th e cause c f these spa tial vari ation isals o discu ssed .